2016
DOI: 10.1007/s10616-016-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antiproliferative effects of different solvent fractions from Terminalia belerica Roxb. fruit on various cancer cells

Abstract: Terminalia belerica Roxb. fruits have been previously reported against diabetes, ulcer, microbial problems and hepatotoxicity. The present study was aimed to investigate antioxidant and anticancer potential of sequentially fractionated hexane (TBHE), chloroform (TBCE), ethyl acetate (TBEE), butanol (TBBE) and water (TBWE) extracts from the 70% methanolic extract of T. belerica fruits. TBCE, TBEE, TBBE and TBWE showed excellent ROS (reactive oxygen species) and RNS (reactive nitrogen species) scavenging activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is evident that the more functional fractions harbour more of antioxidant constituents which are polyphenolic in T. avicennioides. However, Basu et al (2017) in their study showed polar fractions to have more antioxidant action. Akter et al (2019) also showed more polar (methanol and water) extracts to have the highest antioxidant activity, contrary to our study.…”
Section: Discussionmentioning
confidence: 83%
“…It is evident that the more functional fractions harbour more of antioxidant constituents which are polyphenolic in T. avicennioides. However, Basu et al (2017) in their study showed polar fractions to have more antioxidant action. Akter et al (2019) also showed more polar (methanol and water) extracts to have the highest antioxidant activity, contrary to our study.…”
Section: Discussionmentioning
confidence: 83%
“…Many studies indicated that Terminalia chebula Retz has anti-inflammatory and anti-cell proliferation effects and contributed this effect to the phenolic compound of this extract [ 35 , 37 , 93 ]. Terminalia bellerica Retz has also shown anti-cell proliferation effect [ 94 , 95 ]. Dorema ammoniacum D. Don gum showed to have anti-inflammatory effects by inhibiting anti-inflammatory mediator release in animal studies [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ethyl acetate extracts showed the highest DPPH scavenging radical activity with an IC 50 value of 7.11 ”g/mL. The authors mention that the polar fractions showed higher antioxidant activity might be related to the presence of compounds like (114) purpurin, (87) catechin, (89) tannic acid, (88) reserpine, (4) ellagic acid, (70) methyl gallate, and (118) rutin ( Basu et al., 2017 ). Furthermore, Dawe et al.…”
Section: Pharmacological Effects Of Active Constituents From mentioning
confidence: 99%